Enhancing the Student's Reasoning Ability in Solving Real Number System Problems Using the Concept Map. (August 2019) - Khotimah, R P; Masduki,; Sungkono, J
Abstract: The reasoning is an important aspect of learning mathematics. In studying real analysis, students must have the reasoning ability to understand the concepts and the relation of each other. The aim of this research is to examine the effect of using a concept map for learning on the student reasoning ability in solving a real number system problem. The reasoning can be seen from the indicators: analysis, synthesis, verification, and generalization. This research is quantitative research with pre-test post-test group design. The subject of this research is eighteen students who enrolled in a real analysis course in the Department of Mathematics Education, Universitas Widya Dharma Klaten academic year 2017/2018. The data was collected by test and documentation. The reasoning test was given twice, first is the pre-test that was given before the implementation of the concept map model in the learning process, and the second is post-test that given after the implementation of the model. The data were analyzed by descriptive statistics. The results showed that there was an enhancement of student reasoning ability in solving real number system problems by using a concept map